Role of Leishmania (Leishmania) chagasi amastigote cysteine protease in intracellular parasite survival: studies by gene disruption and antisense mRNA inhibition - Mundodi, Vasanthakrishna (BioMed Central, 2005)
BACKGROUND: The parasitic protozoa belonging to Leishmania (L.) donovani complex possess abundant, developmentally regulated cathepsin L-like cysteine proteases. Previously, we have reported the isolation of cysteine protease gene, Ldccys2 from Leishmania (L.) chagasi. Here, we have further characterized this cysteine protease gene and demonstrated its role during infection and survival of Leishmania (L.) chagasi within the U937 macrophage cells. RESULTS: The amastigote specific Ldccys2 genes of L. (L.) chagasi and L. (L.) donovani have identical gene organization, as determined by southern blots. In vivo expression analyses by Northern blots showed that Ldccys2 is amastigote specific. Western blot using anti-Ldccys2 antibody confirmed the amastigote specific protein expression. Recombinant expression of Ldccys2, a 30 kDA protein, was functionally active in a gelatin assay. Results from Ldccys2 heterozygous knockout mutants showed its role during macrophage infection and in intra-macrophage survival of the parasites. Since attempts to generate null mutants failed, we used antisense RNA inhibition to regulate Ldcccys2 gene expression. Not surprisingly, the results from antisense studies further confirmed the results from heterozygous knockout mutants, reiterating the importance of amastigote specific cysteine proteases in Leishmania infection and pathogenesis. CONCLUSIONS: The study shows that Ldccys2 is a developmentally regulated gene and that Ldccys2 is expressed only in infectious amastigote stages of the parasite. The collective results from both the heterozygous knockout mutants and antisense mRNA inhibition studies shows that Ldccys2 helps in infection and survival of L. (L.) chagasi amastigotes within the macrophage cells. Finally, antisense RNA technique can be used as an alternate approach to gene knockout, for silencing gene expression in L. (L.) chagasi, especially in cases such as this, where a null mutant cannot be achieved by homologous recombination.